2020
DOI: 10.1111/nin.12390
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nurses’ experiences in relation to surgical patient safety: A qualitative study

Abstract: Surgical patient safety remains a concern worldwide as, despite World Health Organization recommendations and implementation of its Surgical Safety Checklist, adverse events continue to occur. The aim of this qualitative study was to explore the views and experiences of perioperative nurses regarding the factors that impact surgical patient safety. Data were collected through five focus groups involving a total of 50 perioperative nurses recruited from four public hospitals in Spain. Content analysis of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…[ 28 29 ] Peñataro-Pintado et al . (2021)[ 30 ] reported that some of the key issues that affected the perioperative nurses’ ability to achieve their duties and guarantee patient safety were the stress of working in the operating room, unsuccessful announcement in the multidisciplinary group, and time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 29 ] Peñataro-Pintado et al . (2021)[ 30 ] reported that some of the key issues that affected the perioperative nurses’ ability to achieve their duties and guarantee patient safety were the stress of working in the operating room, unsuccessful announcement in the multidisciplinary group, and time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a detailed analysis of the instrument was reported to promote its use. Thus, we are making a contribution to the previous work by the EORNA [ 18 , 21 ] through the creation of a questionnaire that was designed by perioperative nurses and experts in the area of safety.…”
Section: Discussionmentioning
confidence: 99%
“…In the first round, the theoretical framework of the EORNA was adopted [ 17 ], and five focus groups were developed with perioperative nurses from Spain, which dealt with key aspects of surgical patient safety [ 18 ] between June 2017 and February 2018.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most important ways to improve safety culture and minimize medical errors is teamwork. A study found that the best way to increase patient safety culture is clear, effective communication and teamwork (Peñataro-Pintado et al, 2020). In a study using reports from 29,747 nurses, researchers found that the level of collaboration in a unit had a significant impact on nurse job satisfaction and turnover intention, and quality of care; and it was emphasized that this relationship is independent of nurses' employee characteristics and organizational characteristics (Ma, Shang & Bott, 2015).…”
Section: Introductionmentioning
confidence: 99%